Preemptive Analgesia for Postoperative Hysterectomy Pain Control: Systematic Review and Clinical Practice Guidelines. Issue 2 (June 2018) - Steinberg, A.C.; Schimpf, M.O.; White, A.B.; Mathews, C.; Ellington, D.R.; Jeppson, P.; Crisp, C.; Aschkenazi, S.O.; Mamik, M.M.; Balk, E.M.; Murphy, M.
Abstract : ( Am J Obstet Gynecol . 2017;217(3):303–313) Preemptive analgesia, which may include multimodal pain management, is administered before surgery and is believed to prevent central sensitization. This can include narcotic or non-narcotic medications and may be administered in many ways. This systematic review used current studies of women receiving preemptive medication for abdominal hysterectomy, with a primary outcome of pain control. The aim was to determine the best method of pain control while decreasing narcotic consumption and adverse events.